Productive Growing System of Andrographis paniculata and Inhibitions of Reverse Transcriptase and 3CLpro Enzymes by the Isolated Andrographolide - Kaewsrichan, Jasadee; Wongwitwichot, Paweena; Tipmanee, Varomyalin; Pengnoo, Ashara (Discoveries in Agriculture and Food Sciences, 2024)
Molecular interactions between andrographolide (ADP) and proteins/enzymes of different pathogenic viruses were computationally predicted by using docking method. Binding energy corresponded to a protein-ADP pairing was theoretically accounted in comparison with other current antiviral drugs as positive ligands. In silico, interactions between ADP and PLpro (PDB, 6WX4), ADP and 3CLpro (PDB, 7LMD), ADP and ACE-2 receptor-spike protein complex (PDB, 6M0J), as well as ADP and M2 protein (PDB, 6BKK) were stronger than those of between rimantadine, remdesivir, lopinavir, or ritonavir and the described proteins. The inhibitions of ADP against reverse transcriptase and 3CLpro activities were greater than those of lopinavir, ritonavir, and oseltamivir, according to in vitro assays. ADP was isolated as a major active compound from Andrographis paniculata grown outdoor in newly established, cost-effective, hydroponic system. An average fresh mass per plant was as high as 170 g from a 35x35 cm2 spacing hole. Simple and productive procedures were recently suggested for ADP extraction. These acquired data would be applied for pharmaceutical manufacturing.